2016
DOI: 10.1371/journal.pone.0162953
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Leukocyte Composition between Women before and after Menopausal Age, and Distinct Sexual Dimorphism

Abstract: There are sex differences in many inflammatory and immune diseases, and the differences tend to diminish after menopause. The underlying reasons are unclear, but sex hormone levels are likely to be an important factor. Blood leukocyte count and composition provide an indicator of the inflammatory and immune status of an individual. We performed a cross-sectional analysis of blood leukocyte data from 46,879 individuals (26,212 men and 20,667 women, aged 18 to 93 years) who underwent a routine health checkup. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
73
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 42 publications
18
73
1
3
Order By: Relevance
“…The age trends observed in our study, including different patterns before and after 60 years of age, are comparable with previous reports (Flegar-Mestric et al, 2000;Cheng et al, 2004). In particular, our results are consistent with a recent cross-sectional study that examined peripheral leucocytes in an Asian population (Chen et al, 2016) and found that lymphocyte percentages were higher and neutrophil percentages were lower among men compared to women before age 60 years, but were reversed thereafter. These age-sex patterns could be largely due to sex hormone levels, as suggested by several studies (Bain & England, 1975;Medina et al, 2000;Molloy et al, 2003;Perez-de-Heredia et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The age trends observed in our study, including different patterns before and after 60 years of age, are comparable with previous reports (Flegar-Mestric et al, 2000;Cheng et al, 2004). In particular, our results are consistent with a recent cross-sectional study that examined peripheral leucocytes in an Asian population (Chen et al, 2016) and found that lymphocyte percentages were higher and neutrophil percentages were lower among men compared to women before age 60 years, but were reversed thereafter. These age-sex patterns could be largely due to sex hormone levels, as suggested by several studies (Bain & England, 1975;Medina et al, 2000;Molloy et al, 2003;Perez-de-Heredia et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Declining lymphocyte percentages after the age of 60 years in both sexes can be largely ascribed to both the myeloid bias of HSC differentiation potential (Pang et al , ) and decrease in thymic T‐cell production in aging individuals. Consistent with a recent report (Chen et al , ), immunological aging, as it appears in the proportion of peripheral leucocytes, might become apparent at the age of around 60 years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, PGS for about half of blood cell traits showed different levels of stratification for men and women with 10 blood cell traits with a Bonferroni-adjusted significant interaction between sex and PGS ( Table 1). For example, white blood cell indexes in women significantly decrease after menopause age, while the level of these traits in men were relatively stable 44 . Importantly, in both men and women, the EN-trained PGSs continued to stratify the trait levels even after the trait levels themselves changed.…”
Section: Resultsmentioning
confidence: 99%
“…Inclusion criteria were as follows: randomized controlled trials (RCTs) and non-randomized controlled trials (NRCTs), interventions that use acute or chronic aerobic exercise, which analyze certain markers of the immune system, and healthy adults of both sexes aged between 20 and 45 years. This age group excluded adolescent individuals and menopausal women due to immunological interference (Giefing-Kröll et al, 2015;Chen et al, 2016;Brazil Ministry of Health, 2018). There were no restrictions for language or year of publication in the inclusion of the articles.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%